Ethnic Diversity on Boards of Directors and its Implications on Firm Financial Performance - Marimuthu, Maran (2008)
This paper makes an attempt to understand the extent to which ethnic diversity in top level management affects firm financial performance. Thus, the purpose of this paper is to empirically examine the relationship between ethnic diversity on boards of directors with firm financial performance. This paper uses secondary data from the top 100 non-financial companies listed on the Main Board over a period of 2000 to 2005 (six years). It involves a non-probability sampling as there is a need to meet some specific criteria and requirements. Top 100 companies are determined by ranking them based on their market capitalization. Relevant concepts, propositions and a hypothesis are developed to suit the parametric statistical procedures. Ethnic diversity is measured by the percentage of Non-Malay directors and performance is viewed in terms of Return on Asset (ROA) and control variables are also considered. Statistical techniques such as correlation and regression analyses are considered and the details of the findings explain the impact of ethnic diversity on firm financial performance. This paper is expected to make a significant contribution to the workforce diversity literature particularly at top level management by proving that ethnic diversity on boards of directors is more likely to lead to superior financial performance.